Synthesis and Study the Biological Activity of New Heterocyclic Compounds Derived From Hydrazide Derivatives - Wasan M. Abd-AL Hameed1 , Jumbad H. Tomma2, Rajaa K. Baker3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
The work involves synthesis of new compounds derived from 2-substituted-3-thio- acetohydrazide1,2,4-triazin. The subsituted hydrazine thiocarbothioamide [IV] was obtained via reaction of hydrazidecompound [III] with ammonium thiocyanate and HCl. The cyclization of compound [IV] in 4% NaOH ledto formation 1,2,4-triazoles [V], which were refluxed with chloro-ethylacetate in ethanol and sodium acetateto give compound [VI]. Condensation of ester-compound [VI] with hydrazine (80%) led to formation newhydrazide compounds [VII]. Ring closure reaction of compound [VII] with 4-aminbenzoic acid in POCl3give 1,3,4-oxadiazoles [VIII]. Compound [VIII] wasreacted with sub. benzaldehyde to form compounds ofSchiff bases [IX]a-d. The synthesized compounds were diagnosed via IR, Mass and 1HNMR spectral data.Many of synthesized compounds were examined against activity of antibacterial: gram (+) (Bacillus subtitis,staphylococcus aureus) and gram (-): (E.coli bacteria) and candida tropicalis fungial. To ensure the safety ofthe synthesis compounds the toxicity was examined.